Investigating the effects of red fox management on poultry beyond the controversy, Jura Massif, France - Didier Pépin; Pierre Feuvrier; Thibaut Powolny; Patrick Giraudoux (Scientific Reports)
Abstract The red fox (Vulpes vulpes) is one of the most common generalist mesopredators. Its legal status is often at the centre of controversy between those who wish to protect it and those who wish to control its numbers. In France, foxes are legally hunted and can also be classified as a "species likely to cause damage" (ESOD), the latter status allowing them to be shot and trapped throughout the year. There are a number of legal reasons for this, including damage to poultry. Here, we report the results of a 3.8-year experiment comparing two areas where the fox is protected with areas where it is classified as ESOD. Fox populations were monitored for 4 years before and during the experiment and 231 henhouses were surveyed. 1105 birds were predated in 109 of the 231 henhouses, with an average permanent poultry population of 10,883. 48.3% of damage could be attributed to the category ‘fox’ or ‘likely fox’. Our results show that ESOD status, in the local context, did not lead to a significant reduction in fox numbers or differences in damage rates between areas. However, top and bottom fence protection of outdoor runs significantly reduced fox predation. Better protection for poultry should come from increased security of sheds and outdoor runs, rather than from management of the fox population. The role of dedicated multi-stakeholder working groups for such an evidence-based management at local level is also discussed.